1998
DOI: 10.1111/j.2042-3306.1998.tb05140.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological correlates associated with cribbing behaviour in horses: changes in thermal threshold, heart rate, plasma β‐endorphin and serotonin

Abstract: Summary The aim of the present study was to obtain information on the possible mechanisms underlying cribbing behaviour in horses. To investigate the horse's responsiveness to an external stimulus, a device for telemetric measurement of thermal threshold, using the forelimb withdrawal reflex, was developed and validated. Measurements of thermal threshold took place in cribbing horses (n = 11) before and during cribbing periods. Heart rate was monitored continuously in the same horses. Blood samples were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 25 publications
3
42
0
1
Order By: Relevance
“…The pre-competition mean b-endorphin concentrations recorded in this study were low, although they were consistent with resting values reported in horses, including jumpers [39][40][41]43], and with the minimum plasma b-endorphin concentrations identified at 8:00 AM during a 24-hour sampling period [26].…”
Section: Discussionsupporting
confidence: 87%
“…The pre-competition mean b-endorphin concentrations recorded in this study were low, although they were consistent with resting values reported in horses, including jumpers [39][40][41]43], and with the minimum plasma b-endorphin concentrations identified at 8:00 AM during a 24-hour sampling period [26].…”
Section: Discussionsupporting
confidence: 87%
“…Studies investigating the effect of crib-biting on the SAM axis reactivity found similar results for HR as we found for the HPA axis. For instance, HR was shown to decrease during bouts of crib-biting [17,19]. Differences between cribbiters and controls in heart rate variability have also been found in other studies [7].…”
Section: Sam Axis Response Of Crib-biters and Controlssupporting
confidence: 68%
“…Previous studies that have investigated whether stereotypies lowered arousal and anxiety as well as corticosteroid levels, did not find consistent results [7,[17][18][19][20]. If crib-biting is indeed a coping mechanism, animals should show signs of stress in situations in which they are prevented from crib-biting.…”
Section: Hpa Axis Response Of Crib-biters That Did and Did Not Crib-bitementioning
confidence: 93%
See 1 more Smart Citation
“…Reported PPP serotonin values in healthy horses range from 2.5 ng/ml to 90 ng/ml with a majority varying between 3 ng/ml and 30 ng/ml. 1,2,4,6,7,13,[17][18][19]21 One possible explanation for this inconsistency is the use of different analytical techniques. Therefore, it is essential to develop fast and reliable detection methods, which are well validated for use on equine plasma samples.…”
Section: Introductionmentioning
confidence: 99%